Implementasi Strategi Bauran Pemasaran Marketing Mix Pada Mikari Bakery - Hermika Pinem; Indri Sri Asdini Silaban; Monika Ayu Lumbantoruan; Lenti Susanna Saragih (Pusat Riset dan Inovasi Nasional, 2023)
The marketing mix strategy in business scope combines eight marketing mix elements, which include product, price, place and promotion, people, processes, physical evidence, public opinion to achieve business goals. So the aim of this research is to face global markets and technological changes, this research provides important insights into effective marketing tactics, the challenges faced by companies as well as optimizing marketing mix strategies in this era to achieve competitive advantage